2006
DOI: 10.1002/bit.20898
|View full text |Cite
|
Sign up to set email alerts
|

Visible laser and UV‐A radiation impact on a PNP degrading Moraxella strain and its rpoS mutant

Abstract: The role of stationary phase sigma factor gene (rpoS) in the stress response of Moraxella strain when exposed to radiation was determined by comparing the stress responses of the wild-type (WT) and its rpoS knockout (KO) mutant. The rpoS was turned on by starving the WT cultures for 24 h in minimal salt medium. Under non-starved condition, both WT and KO planktonic Moraxella cells showed an increase in mortality with the increase in duration of irradiation. In the planktonic non-starved Moraxella, for the powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…To date, light emitting diodes (LEDs) as a preferred light source for phototherapy have been used to treat dermatitis and muscle analgesia, as well as to remove bacteria in vitro (Desmet et al, ; Lim et al, ; Nandakumar, Keeler, Schraft, & Leung, ). In particular, blue LEDs with wavelengths of 400–500 nm have been used for treatment in hyperbilirubinemia of infantile jaundice (Ennever, McDonagh, & Speck, ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, light emitting diodes (LEDs) as a preferred light source for phototherapy have been used to treat dermatitis and muscle analgesia, as well as to remove bacteria in vitro (Desmet et al, ; Lim et al, ; Nandakumar, Keeler, Schraft, & Leung, ). In particular, blue LEDs with wavelengths of 400–500 nm have been used for treatment in hyperbilirubinemia of infantile jaundice (Ennever, McDonagh, & Speck, ).…”
Section: Introductionmentioning
confidence: 99%
“…Visible light lasers have been used as bactericidal agents to remove bacterial biofilms (Nandakumar et al, 2006). Recently, Hamblin et al (2005) also showed that high intensity visible light could kill Heliobacter pylori in the stomach of humans.…”
Section: Introductionmentioning
confidence: 99%
“…Light emitting diodes (LEDs) have been applied to replace traditional lights with lower cost and spectrum variability. A visible spectrum has been clinically tried to control pain in dermatitis, Alzheimer's disease, muscle analgesia and bacterial infection in vitro . Recent studies have been reported that red LED irradiation has anti‐inflammatory and antitumor activities by suppression of cytokine production in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%